2018
DOI: 10.5194/os-2018-14
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of North Balearic Front during an autumn Tramontane and Mistral storm: air–sea coupling processes and stratification budget diagnostic

Abstract: Abstract. The north Balearic front forms the southern branch of the cyclonic gyre in the North Western Mediterranean Sea. Its dynamics exhibits significant seasonal variability. During autumn, the front spreads northward during the calm wind periods and rapidly moves back southward when it is exposed to strong northerly wind events such as the Tramontane and Mistral. These strong winds considerably enhance the air–sea exchanges. To investigate the role of air–sea exchanges on the dynamics of the North Balearic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…In Wesselmann et al (2018), the authors revealed genetic differentiations between Banyuls‐Murcia and Banyuls‐Mallorca likely due to isolation by distance and to the North Balearic Front which creates a physical barrier of dense water that limits the circulation of particles such as larvae (Seyfried et al, 2019). The source population of individuals in the bay of Peyrefite was thus more likely located in the Eastern or Northeastern part of the Gulf of Lion, such as the northern lagoons (Salses‐Leucate and Thau), and larvae may be transported by the influence of the Northern Current (Seyfried et al, 2019). Such low levels of self‐recruitment and high connectivity were also found at a similar spatial scale for other bivalve species such as the Arctic surfclam, Mactromeris polynyma (Cassista & Hart, 2007), the Venus clam Polititapes rhomboides (Chacón et al, 2021), or the hard clam Meretrix meretrix (Ye et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Wesselmann et al (2018), the authors revealed genetic differentiations between Banyuls‐Murcia and Banyuls‐Mallorca likely due to isolation by distance and to the North Balearic Front which creates a physical barrier of dense water that limits the circulation of particles such as larvae (Seyfried et al, 2019). The source population of individuals in the bay of Peyrefite was thus more likely located in the Eastern or Northeastern part of the Gulf of Lion, such as the northern lagoons (Salses‐Leucate and Thau), and larvae may be transported by the influence of the Northern Current (Seyfried et al, 2019). Such low levels of self‐recruitment and high connectivity were also found at a similar spatial scale for other bivalve species such as the Arctic surfclam, Mactromeris polynyma (Cassista & Hart, 2007), the Venus clam Polititapes rhomboides (Chacón et al, 2021), or the hard clam Meretrix meretrix (Ye et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…nobilis population structure which suggested high levels of connectivity across the Gulf of Lion (González‐Wangüemert et al, 2019; Peyran, Boissin, et al, 2021; Wesselmann et al, 2018). In Wesselmann et al (2018), the authors revealed genetic differentiations between Banyuls‐Murcia and Banyuls‐Mallorca likely due to isolation by distance and to the North Balearic Front which creates a physical barrier of dense water that limits the circulation of particles such as larvae (Seyfried et al, 2019). The source population of individuals in the bay of Peyrefite was thus more likely located in the Eastern or Northeastern part of the Gulf of Lion, such as the northern lagoons (Salses‐Leucate and Thau), and larvae may be transported by the influence of the Northern Current (Seyfried et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…During the second period of 27-28 October 2012, the cyclone center reached the lowest pressure of 985 hPa over the Alps (Fig. 2) associated with a clear trough in the upper troposphere, provoking severe northwesterly-northerly winds advecting cold and dry air over the WMed Sea and inducing large evaporation as well as ocean cooling and mixing (Lebeaupin Brossier et al, 2014;Rainaud et al, 2015Rainaud et al, , 2017Seyfried et al, 2019). The relationship between cyclone dynamics and heavy rainfall during IOP16 is discussed in detail by Flaounas et al (2016).…”
Section: Illustrative Case: Iop16mentioning
confidence: 99%
“…During the second period, 27−28 October 2012, the cyclone centre reached the lowest pressure of 985 hPa over the Alps (Fig. 2), associated with a clear trough in the upper troposphere and provoking severe northwesterly/northerly winds advecting cold and dry air over the WMed Sea and inducing large evaporation and ocean cooling and mixing (Lebeaupin Brossier et al, 2014;Rainaud et al, 2015Rainaud et al, , 2017Seyfried et al, 2018). The relationship between cyclone dynamics and heavy rainfall during IOP16 is discussed in detail by Flaounas et al (2015a).…”
Section: Illustrative Case: Iop 16mentioning
confidence: 99%